School staff perceptions of the nature and consequences of students' use of e‐cigarettes - Simone Pettigrew; Mia Miller; Anjali Kannan; Thout Sudhir Raj; Min Jun; Alexandra Jones (Elsevier, 2022)
Abstract Objective: The aim of this study was to assess the nature and consequences of student vaping in Australian primary and secondary schools by consulting staff working in these settings. Methods: A national sample of 196 school staff was accessed via a web panel provider and administered an online survey about students' e‐cigarette use. Three‐quarters of the survey respondents were teachers/teacher aides, with the remainder divided between those in other student‐facing roles and office staff. Results: A majority (78%) of respondents expressed concern about current levels of vaping in schools. Around half reported negative outcomes relating to mental well‐being, social/peer interactions, and school performance. Only one‐third of respondents reported a vaping policy (35%) or vaping‐prevention education (31%) being in place at their schools. Conclusions: E‐cigarette use in schools is an area of concern for school staff, yet relevant policies and education programs appear to be lacking. Implications for public health: Schools represent a key context for encouraging health promoting behaviours and discouraging harmful behaviours, including vaping. These results highlight the need to monitor and address student e‐cigarette use in schools and provide staff with greater support to prevent the negative consequences associated with vaping by children at school and beyond.